Improving the environmental safety of drinking water supply in kharkiv region (Ukraine) - Третьяков, Олег Вальтерович; Шевченко, Тамара Олександрівна; Безсонний, Віталій Леонідович (Eastern-European Journal of Enterprise Technologies, 2015)
The current poor state of water bodies testifies to the fact that the problems of water protection from pollution and depletion have not been solved and even significantly aggravated, especially in recent years. We have studied the quality of water and the ecological state of surface sources of drinking water supply in Kharkiv region and made a retrospective analysis of the chemical composition of the waste water that was released into the Siversky Donets by the Izyum Municipal Industrial Water Supply and Sewerage Company from 2008 to 2014. We have revealed the sustainable trends of worsening efficiency of wastewater treatment plants in the sanitation system of Izyum, which has, consequently, led to a significant deterioration in water quality and ecological state of the Siversky Donets that is the source of drinking water for settlements of three regions of Ukraine: Kharkiv, Donetsk, and Luhansk. We have suggested the basic ways to improve the water quality in the Siversky Donets and the ecological state of the entire region, which include: (1) a major reconstruction of sewage treatment plants in Izyum in order to improve the ecological state of the Siversky Donets basin and achieve the required quality of the surface water sources as well as (2) provision of a system of the state continuous monitoring of surface water in the Siversky Donets basins, within Kharkiv, Donetsk and Luhansk regions, to promptly identify the polluting enterprises, institutions and organizations and timely use the leverage provided by the current legislation of Ukraine.